Pengaruh Manajemen Risiko, Pengendalian Internal dan Sistem Akuntansi Terhadap Efektivitas Kredit - Kadek Dewi Styawati (UNHI Press, 2022)
The purpose of this study was to examine the effect of implementing risk management, internal control, and accounting systems on the effectiveness of lending to Rural Banks (BPR) throughout Gianyar Regency. The population is all employees at 22 BPR units throughout Gianyar Regency as many as 808 people. The sample was determined using purposive sampling as many as 151 people. Data were analyzed using multiple linear regression analysis. The results of the analysis show that the application of risk management, internal control, and accounting systems have a positive and significant effect on the effectiveness of lending to Rural Banks (BPR) throughout Gianyar Regency.